Transient Receptor Potential Channels and Inflammatory Bowel Disease - Chen, Yiding; Mu, Jingxi; Zhu, Min; Mukherjee, Arjudeb; Zhang, Hu (Frontiers in Immunology, 2020)
Abstract The transient receptor potential (TRP) cation channels are present in abundance across the gastrointestinal (GI) tract, serving as detectors for a variety of stimuli and secondary transducers for G-protein coupled receptors. The activation of TRP channels triggers neurogenic inflammation with related neuropeptides and initiates immune reactions by extra-neuronally regulating immune cells, contributing to the GI homeostasis. However, under pathological conditions such as inflammatory bowel disease (IBD), TRP channels are involved in the intestinal inflammation. An increasing number of human and animal studies have indicated that TRP channels are correlated to the visceral hypersensitivity (VHS) and immune pathogenesis in IBD, leading to exacerbation or amelioration of the VHS or intestinal inflammation. Thus, TRP channels are a promising target for novel therapeutic methods for IBD. In this review, we comprehensively summarize the functions of TRP channels, especially their potential roles in immunity and IBD. Additionally, we discuss the contradictory findings of prior studies and offer new insights with regard to future research.